THE SUSTAINABILITY OF PESANTREN FINANCING MANAGEMENT BASED ON ISLAMIC ENTREPRENEURSHIP - Faiqotul Aminah, Akmal Mundiri, Hefniy, Maripaz C. Abas (JINGJI : Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This study aims to explore in depth the role of Islamic boarding school entrepreneurshipin supporting the sustainability of education financing and to understand how specificstrategies are implemented at Al-Mashduqiah Islamic Boarding School in order tomaintain the sustainability or development of business units in the future. The methodused in this study is qualitative with a case study approach, which emphasizes contextualand in-depth analysis without being tied to numbers or calculations. The data usedincludes primary data obtained through in-depth interviews with Islamic boarding schoolleaders, foundation administrators, and related parties in financial management, as wellas secondary data taken from articles, scientific journals, and other relevant documents.Data collection techniques include in-depth interviews and participatory observation,which allow researchers to understand the role of Islamic boarding school business unitsin supporting operations, challenges faced, and innovations implemented to maintain thesustainability of Islamic boarding school financing.